Epidemiology and Self‐Treatment of Travelers' Diarrhea in a Large, Prospective Cohort of Department of Defense Beneficiaries. Issue 3 (7th December 2014) - Lalani, Tahaniyat; Maguire, Jason D.; Grant, Edward M.; Fraser, Jamie; Ganesan, Anuradha; Johnson, Mark D.; Deiss, Robert G.; Riddle, Mark S.; Burgess, Timothy; Tribble, David R.; ,
Abstract : Background: Infectious diarrhea is a common problem among travelers. Expert guidelines recommend the prompt use of antibiotics for self‐treatment of moderate or severe travelers' diarrhea (TD). There is limited data on whether travelers follow these self‐treatment guidelines. We evaluated the risk factors associated with TD, the use of TD self‐treatment, and the risk of irritable bowel syndrome (IBS) during travel. Methods: Department of Defense beneficiaries traveling outside the United States for ≤6.5 months were enrolled in a prospective cohort study. Participants received pre‐ and post‐travel surveys, and could opt into a travel illness diary and follow‐up surveys for symptoms of IBS. Standard definitions were used to assess for TD and IBS. Suboptimal self‐treatment was defined as the use of antibiotics (with or without antidiarrheal agents) for mild TD, or the use of antidiarrheals alone or no self‐treatment in cases of moderate or severe TD. Results: Twenty‐four percent of participants (270/1, 120) met the criteria for TD. The highest incidence was recorded in Africa [8.6 cases/100 person‐weeks, 95% confidence interval (CI): 6.7–10.5]. Two hundred and twelve participants with TD provided information regarding severity and self‐treatment: 89 (42%) had mild TD and 123 (58%) had moderate or severe TD. Moderate or severe TD was independently associated with suboptimal self‐treatment [OR 10.4 (95% CI: 4.92–22.0)]. Time to last unformed stool did not differ between optimal and suboptimal self‐treatment. IBS occurred in 4.5% (7/154) of TD cases and in 3.1% (16/516) of cases without TD ( p = 0.39). Among TD cases, a lower incidence of IBS was noted in participants who took antibiotics [4.8% (5/105) vs 2.2% (1/46)] in those who did not, but the difference did not reach statistical significance ( p = 0.60). Conclusions: Our results suggest the underutilization of antibiotics in travelers with moderate or severe TD. Further studies are needed to systematically evaluate pre‐travel instruction and traveler adherence to self‐treatment guidelines, and the impact of suboptimal self‐treatment on outcomes.